2019
DOI: 10.1186/s13063-019-3586-y
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral oxygen saturation and postoperative delirium in endovascular surgery: a prospective cohort study

Abstract: Background Delirium is an acute mental disorder and common postoperative complication. Monitoring regional cerebral oxygen saturation (rSO 2 ) in endovascular therapeutic surgery may allow real-time monitoring of cerebral desaturation, avoiding profound cerebral dysfunction, and reducing the incidence of delirium. We sought to examine the incidence of delirium in patients undergoing endovascular surgery. Methods This was a clinical cohort tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Continuous monitoring of rSO 2 using the NIRS can reflect the oxygen supply, oxygen consumption, and cerebral perfusion on time (16). Studies have shown that decreased intraoperative rSO 2 is significantly associated with postoperative neurological dysfunction (17)(18)(19). A prospective cohort study including 43 patients undergoing cerebral endovascular surgery showed that the decrease of rSO 2 can be used to predict delirium and that the continuous monitoring of rSO 2 can reduce the incidence of postoperative delirium (19).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous monitoring of rSO 2 using the NIRS can reflect the oxygen supply, oxygen consumption, and cerebral perfusion on time (16). Studies have shown that decreased intraoperative rSO 2 is significantly associated with postoperative neurological dysfunction (17)(18)(19). A prospective cohort study including 43 patients undergoing cerebral endovascular surgery showed that the decrease of rSO 2 can be used to predict delirium and that the continuous monitoring of rSO 2 can reduce the incidence of postoperative delirium (19).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang X. [ 53 ] evaluated patients once a day, Maheshwari [ 52 ] twice a day, while Neerland [ 33 ] did not perform POD assessment on weekend days, and Soh [ 48 ] observed patients only up to 48 h after surgery. It must be remembered that current guidelines recommend that evaluation should be performed every 8 h or at least once per nurse shift throughout the hospitalization [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patti et al [ 42 ] the recognized IOH also in the case of long-term intraoperative use of catecholamines. In the remaining 7 studies the lowest intraoperative MAP, SBP or DBP [ 33 , 45 , 47 , 53 , 54 ] values were assessed or different strategies of intraoperative BP management were evaluated [ 39 ]. Furthermore, the authors applied various methods of BP monitoring: invasive and non-invasive, and additionally, used different time intervals for measurements, ranging between 1 and 15 min, which means that shorter episodes of hypotension could have been missed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 The rSO 2 value is a very sensitive indicator of cerebral hypoxia, which can cause cerebral hypoperfusion, resulting in POD. 11 , 12 At present, there is no unified standards for the optimal FiO 2 in operation, which is 30% ~ 100% in clinical operation. However, for elderly patients undergoing laparoscopic abdominal surgery, no unified conclusion has been reached on the effects of different FiO 2 on POD.…”
Section: Introductionmentioning
confidence: 99%